Cancer clinical trial providers’ perspectives on communicating goals of care: A key informant study - Wen-Ying Sylvia Chou; Angela L. Falisi; Kathleen Castro; Rebecca A. Ferrer; Anna Gaysynsky; Grace C. Huang; Michelle A. Mollica; Emily B. Peterson; Erin E. Kent (PEC Innovation, 2022)
Objectives: There has been limited research to date exploring provider communication in the context of cancer clinical trials. To elucidate multidisciplinary care providers’ experiences, this qualitative study sought to understand their perspectives and communication patterns around goals of care discussions with patients enrolled in cancer clinical trials. Methods: Semi-structured key informant interviews were conducted with a purposive sample of physicians, nurse practitioners, social workers, chaplains, nurses, and administrative staff in a cancer research hospital (N=19). Data were analyzed and interpreted using thematic analysis. Results: Providers hold varied perspectives on goals of care in cancer clinical trials, highlighting the tension and potential for misalignment between scientific and clinical (patient-centered) goals. Inherent institutional hierarchies may impede some team members from initiating goal discussions. Care transitions (e.g., stopping treatment or initiating hospice) offer critical opportunities for goals of care discussions. Conclusion: Conflicting perspectives among team members, perceptions of provider roles, and communication patterns could help explain some of the communication challenges previously documented in advanced cancer and clinical trial care. Innovation: This qualitative study contributes to the literature on healthcare team communication in the clinical trial context and highlights tangible opportunities to better leverage providers’ diverse experience and improve patient-centered care.